ASSESSMENT OF EARLY CHILDHOOD EDUCATORS’ COMPETENCE IN FACILITATING SCIENTIFIC PLAY- LEARN ACTIVITIES IN EARLY CHILDHOOD EDUCATION CENTRES IN DELTA STATE - Balota, Ifelayo; Olajide, Simeon (Advances in Social Sciences Research Journal, 2021)
Abstract The study identified the scientific play-learn activities practiced in early childhood education centres in Delta state and investigated the academic qualifications of the early childhood educators. It also assessed the scientific play-learn skills of the early childhood educators and examined the relationship between early childhood educators’ qualifications and scientific play-learn activities facilitation skills in the study area. These were with a view to providing succinct information about early childhood educators’ competence in facilitating scientific play-learn activities in early childhood centres in the State. The study adopted a descriptive survey research design. The population of the study comprised all early childhood educators in the State. The sample for the study consisted of 360 early childhood educators drawn from the three senatorial districts in the state using multistage sampling procedure. One self-designed instrument titled ‘‘Early Childhood Educators’ Competence in Science Play-learn Activities Questionnaire’’ (ECECSPAQ) was used for data collection. The data collected were analysed using frequency count, percentage, and regression analysis. The results of the study showed that 29.5% of early childhood educators in all the centres practised gravity, 22.3% practised motion, 16.4% practised electricity, 46.4% practised sound, and 24.2% practised air and wind. The results further showed that 16.1 % of the early childhood educators had senior school certificate, 11.4% had ND certificate, 20.6% had TC11 and NCE, 14.4% had HND, 4.7% had certificate in Nursery and Primary education while 10.5% also had certificate in science areas. The results also showed that early childhood educators possessed very low level of scientific play-learn skills (21.90%). The results finally showed a significant relationship of early childhood educators’ qualifications on scientific play-learn activities facilitation skills (F = 2.547, p < 0.05). The study concluded that early childhood educators possessed low competence in embarking on rich scientific play-learn activities necessary to promote science learning in children.